PROFILE OF SELF-ACCEPTANCE OF HIV/AIDS PATIENTS IN WEST JAVA INDONESIA - Siti Sofiah; Mamat Supriatna (Universitas Pendidikan Indonesia, 2022)
This study identifies the weak self-acceptance of people living with HIV/AIDS which results in destructive behavior that results in denial, withdrawal, fear of rejection in the environment, anxiety which adversely affects their mental health, depression, isolation and even suicidal tendencies. The quantitative research method with a cross- sectional design used a self-acceptance questionnaire sampling technique which was adapted based on the theory of Carol Ryff (1996). Participants were one hundred from five hospitals in West Java. The results of the study show that people with HIV/AIDS can accept their condition, although in some aspects they are still in the low category.